Operating Cabled Underwater Observatories in Rough Shelf-Sea Environments: A Technological Challenge - Fischer, Philipp; Brix, Holger; Baschek, Burkard; Kraberg, Alexandra; Brand, Markus; Cisewski, Boris; Riethmüller, Rolf; Breitbach, Gisbert; Möller, Klas Ove; Gattuso, Jean-Pierre; Alliouane, Samir; van de Poll, Willem H.; et al. (Frontiers in Marine Science, 2020)
Cabled coastal observatories are often seen as future-oriented marine technology that enables science to conduct observational and experimental studies under water year round, independent of physical accessibility to the target area. Additionally, the availability of (unrestricted) electricity and an Internet connection under water allows the operation of complex experimental setups and sensor systems for longer periods of time, thus creating a kind of laboratory beneath the water. After successful operation for several decades in the terrestrial and atmospheric research field, remote controlled observatory technology finally also enables marine scientists to take advantage of the rapidly growing communication technology. The continuous operation of two cabled observatories in the southern North Sea and off the Svalbard coast since 2012 shows that even highly complex sensor systems, such as stereo-optical cameras, video plankton recorders or systems for measuring the marine carbonate system, can be successfully operated remotely year-round facilitating continuous scientific access to areas that are difficult to access, such as the polar seas or the North Sea. Experience also shows, however, that the challenges of operating a cabled coastal observatory go far beyond the provision of electricity and network connection under water. In this manuscript, the essential developmental stages of the "COSYNA Shallow Water Underwater Node" system are presented, and the difficulties and solutions that have arisen in the course of operation since 2012 are addressed with regard to technical, organizational and scientific aspects.